Long-active granulocyte colony-stimulating factor for peripheral blood hematopoietic progenitor cell mobilization. (June 2014) - Martino, Massimo; Laszlo, Daniele; Lanza, Francesco
Abstract : Introduction: Peg-filgrastim (PEG-FIL), a polyethylene glycol-conjugated form of granulocyte colony-stimulating factor (G-CSF), has been introduced in clinical practice and is effective in shortening the time of neutropenia after cytotoxic chemotherapy. G-CSF has emerged as the preferred cytokine for hematopoietic progenitor cells' (HPC) mobilization. Nevertheless, data on the ability of PEG-FIL in this field have been published. Areas covered: We review publications in the field with the goal of providing an overview of this approach. Expert opinion: PEG-FIL may be able to mobilize CD34 + cells in a more timely fashion than G-CSF, with the advantages of only a single-dose administration, an earlier start and a reduction in the number of apheresis procedures. The main controversies concern the dosage of the drug and the optimal dose. In the context of chemo-mobilization, a single dose of 6 mg PEG-FIL seems effective in terms of HPC's mobilization and there is no increase in this effect if the dose is doubled to 12 mg. Steady-state mobilization requires higher doses of PEG-FIL and this approach is not cost-effective when compared with G-CSF. The experiences with PEG-FIL in the healthy donor setting are very limited.